Предмет: Алгебра,
автор: FatherPucci
Решить уравнение:
Ответы
Автор ответа:
1
Объяснение:
(х²-2х)²-11(х²-2х)+24=0
пусть (х²-2х)=t, тогда
t²-11t+24=0
D=121-96=25
√D=5
t1=11+5/2=8
t2=11-5/2=3
(х²-2х)=8 или (х²-2х)=3
х²-2х-8=0 х²-2х-3=0
D=4+12=16
√D=4
x1=2+4/2=3
x2=2-4/2=-1
D=4+32=36
√D=6
x1=2+6/2=4
x2=2-6/2=-2
ответ: 4;-2;3;-1
Похожие вопросы
Предмет: Русский язык,
автор: efanova1983
Предмет: Русский язык,
автор: kryukhchina
Предмет: Українська мова,
автор: natashavahmist
Предмет: Русский язык,
автор: Karina5278
Предмет: Математика,
автор: nadia25062222